Seizures in Critical Care : A Guide to Diagnosis and Therapeutics - Varelas, Panayiotis N.; Claassen, Jan (Current Clinical Neurology, 2017)
Updated and expanded to provide the neurologic, intensive and critical care communities a comprehensive guide to common critical care illnesses and seizures, this third edition remains the premier resource on seizures in critical care. In addition to covering etiology, pathophysiology, diagnosis, differential diagnosis and treatment options, chapters feature the latest technologies and treatments and integrate current literature. This unique and specialized text offers neurologists, intensivists, neurosurgeons, trauma surgeons, epileptologists, electrophysiologists and residents in various specialties clarity on this challenging set of comorbidities.